Religious Plurality in Dayak Bidayuh Lara Society (Portrait of Inter-Religious Harmony in Kendaie Lundu Village, Sarawak) - Zakaria Efendi (Jurnal Dialog, 2021)
This study investigates the phenomena of plurality among the Dayak Bidayuh Lara community in Kendaie Lundu Village, Sarawak. Apart from that, it also describes the social and religious activities of the indigenous people that maintain the concept of tolerance. This study used qualitative methods by conducting observations and by using a descriptive approach as a research instrument. The study found that 1) as an indigenous community, the indigenous Dayak Bidayuh lara community in Kendaie Lundu Village are aware of the plurality of life in their environment, so that in carrying out social and religious activities, they live not in boundaries that separate between majority and minority communities. 2) There are some people with different religions from one family and live in one house. So that this reflects the exoticism of religious plurality in the Dayak Bidayuh Lara community; 3) as a community that inhabits the interior and border areas, inter-national fraternities are closely intertwined, social relations between the people of Malaysia and Indonesia are still established today. Makalah ini menggambarkan pluralias yang terjadi pada masyarakat Dayak Bidayuh Lara di Kampung Kendaie Lundu, Sarawak. Selain itu, makalah ini juga mendeskripsikan kegiatan-kegiatan sosial dan keagamaan masyarakat adat di sana yang menjunjung tinggi toleransi. Penelitian ini menggunakan metode kualitatif dengan melakukan observasi, pengamatan, dan dengan menggunakan pendekatan deskriptif sebagai instrumen penelitian. Hasil penelitian; 1) sebagai masyarakat adat, masyarakat adat Dayak Bidayuh Lara di Kampung Kendaie Lundu sadar akan pluralitas dalam kehidupan di lingkungannya, sehingga dalam melakukan aktivitas sosial dan keagamaan, tidak menimbulkan jarak dan batasan antara masyarakat mayoritas dan minoritas; 2) masih banyak dijumpai orang-orang dengan agama yang berbeda namun masih satu keluarga dan hidup dalam satu rumah, sehingga hal tersebut mencerminkan keeksotisan dalam kemajemukan beragama pada masyarakat Dayak Bidayuh lara di sana; 3) sebagai masyarakat yang mendiami wilayah pedalaman dan perbatasan, persaudaraan serumpun lintas negara terjalin dengan erat, hubungan sosial masyarakat di Malaysia dan Indonesia masih terjalin sampai sekarang.